The Effect of Sustainable Production, Green Intellectual Capital, and Green Technology Innovation on Sustainable Finance with Green Strategic Management as a Moderating Variable - Sebastianus Laurens; Khomsiyah Khomsiyah; Titik Aryati (Dinasti Publisher, 2026)
This study aims to examine the effects of sustainable production, green intellectual capital, and green technological innovation on sustainable finance, as well as the moderating role of green strategic management in these relationships. A total of 352 respondents from production companies in Indonesia were randomly selected and participated by completing the questionnaires. Each indicator item in each variable was assessed using an interval scale. The results show positive relationships between sustainable production, green intellectual capital, and green technological innovation with sustainable finance. The positive correlation between sustainable production and sustainable finance can be strengthened by green strategic management. However, green strategic management does not strengthen the relationship between green intellectual capital and sustainable finance, nor between green technological innovation and sustainable finance. This study has implications for production companies in Indonesia that are trying to implement environmentally friendly processes to reduce corporate risk. Innovation and guidance can be implemented for companies that are just starting sustainable production and towards achieving sustainable finance.